Efektivitas Pemungutan Pajak Daerah Melalui Layanan Aplikasi Siapdol - Septiadi, Kusnadi; Sudrajat, Arip Rahman; Lalas, Lalas (Universitas Musamus, Merauke, Papua, 2024)
Effectiveness refers to achieving the goals of government services to the community. Regional tax collection is the process of collecting funds from taxpayers by the local government. Siapdol is a website-based application for information services and tax payments in Sumedang Regency. This research aims to assess the effectiveness of local tax collection through Siapdol at the Regional Revenue Agency of Sumedang Regency using descriptive qualitative research methods and purposive sampling. Data collection techniques include literature study, observation, interviews, and documentation, which are processed through data collection, data reduction, data display, and conclusion drawing/verification. The research results show that the effectiveness of tax collection through Siapdol is quite good, as seen from socialization, management resources, facilities and infrastructure, service mechanisms, ease of access, security and accuracy of tax data. However, its effectiveness is not yet optimal due to limited employee technology skills, availability of internet access, and public awareness. Suggestions for increasing effectiveness include intensive outreach and education to the taxpayer community, periodic updating of facilities and infrastructure, ongoing technical training for employees, as well as development of additional features for periodic monitoring and evaluation.